2011
DOI: 10.1115/1.4005063
|View full text |Cite
|
Sign up to set email alerts
|

Gas Microflows in the Slip Flow Regime: A Critical Review on Convective Heat Transfer

Abstract: Accurate modeling of gas microvection is crucial for a lot of MEMS applications (microheat exchangers, pressure gauges, fluidic microactuators for active control of aerodynamic flows, mass flow and temperature microsensors, micropumps, and microsystems for mixing or separation for local gas analysis, mass spectrometers, vacuum, and dosing valves…). Gas flows in microsystems are often in the slip flow regime, characterized by a moderate rarefaction with a Knudsen number of the order of 10 À2 -10 À1 . In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 87 publications
(177 reference statements)
2
54
0
Order By: Relevance
“…Fukuda et al [15] reported a method for designing microreactors for isothermal operation including heat transfer. Colin [16] presented a critical review indicating the importance of slip boundary conditions and recommendations for the factors affecting heat transfer and fluid flow characteristics at microscale.…”
Section: Introductionmentioning
confidence: 99%
“…Fukuda et al [15] reported a method for designing microreactors for isothermal operation including heat transfer. Colin [16] presented a critical review indicating the importance of slip boundary conditions and recommendations for the factors affecting heat transfer and fluid flow characteristics at microscale.…”
Section: Introductionmentioning
confidence: 99%
“…This reconstruction algorithm has been numerically tested on DSMC generated data. Results help estimating an coefficients which depend on the nature of the gas and the wall (Sharipov 2011) and are a priori unknown; these models lead to more or less complex solutions for heat transfer (Colin 2012) and fluid flow (Zhang et al 2012) in the slipflow regime.…”
Section: Introductionmentioning
confidence: 99%
“…Although they explicitly incorporated the temperature jump in the boundary conditions, it was ignored in the calculation of the eigenvalues (Ezquerra Larrodé, Housiadas & Drossinos 2000). It is crucial to account for the temperature jump at the wall for rarefied gas flows, since the effect of this temperature jump is dominant over the influence of wall slip (Ezquerra Larrodé et al 2000;Colin 2011). …”
Section: Introductionmentioning
confidence: 99%